Lessons Learned from Implementation of the Food Insecurity Screening and Referral Program at Kaiser Permanente Colorado - Stenmark, Sandra Hoyt (Perm J, 2018)
Traditionally, health care systems have addressed gaps in patients’ diet quality with programs that provide dietary counseling and education, without addressing food security. However, health care systems increasingly recognize the need to address food security to effectively support population health and the prevention and management of diet-sensitive chronic illnesses. Numerous health care systems have implemented screening programs to identify food insecurity in their patients and to refer them to community food resources to support food security. This article describes barriers encountered and lessons learned from implementation and expansion of the Kaiser Permanente Colorado’s clinical food insecurity screening and referral program, which operates in collaboration with a statewide organization (Hunger Free Colorado) to manage clinic-to-community referrals. The immediate goals of clinical screening interventions described in this article are to identify households experiencing food insecurity, to connect them to sustainable (federal) and emergency (community-based) food resources, to alleviate food insecurity, and to improve dietary quality. Additional goals are to improve health outcomes, to decrease health care utilization, to improve patient satisfaction, and to better engage patients in their care.